Development of discourse as an instrument of critical social analysis - Pešić, Milena (Sociološki pregled, 2021)
Since the concept of discourse has become almost indispensable in the contemporary research of a large number of social and political phenomena, and as such represents a transdisciplinary instrument of social analysis and critique, it is of indisputable importance to indicate what its theoretical-methodological relevance consists of. For that purpose, the genesis of this polyvalent concept is given in this paper through the developmental presentation of various analytical levels of its consideration within the context of general frameworks of scientific insights relevant for its theoretical operationalization. Particular analytical attention was given to the concepts of Michel Foucault and Jürgen Habermas, not only because those are two of the most influential discourse theories in the twentieth century, but also because the differences between them offer a more comprehensive insight into the importance of this concept.
Keywords: critical analysis; discourse; language; text; power